Artificial Intelligence Applications in Community and Home Nursing Care: A Systematic Literature Review - Berliana Rahmadhani; Purwono Purwono; Muhammad Ahmad Baballe; Isa Ali Ibrahim (LPPM Universitas Harapan Bangsa, 2026)
Healthcare systems face increasing demand for community and home nursing care due to population aging, chronic disease prevalence, and hospital resource limitations. Artificial intelligence (AI) has emerged as a supportive technology with potential to enhance nursing practice in decentralized care environments. This systematic literature review synthesizes recent evidence on AI applications in community and home nursing care. The review followed PRISMA 2020 guidelines and analyzed fifteen peer-reviewed studies published between 2022 and 2025. The findings indicate that machine learning–based predictive analytics and decision-support systems are the most frequently implemented technologies. AI applications primarily support risk prediction, remote monitoring, chronic disease management, and workflow optimization. Reported outcomes include improved clinical vigilance, enhanced care coordination, and increased operational efficiency. However, implementation challenges remain, including infrastructure readiness, digital literacy gaps, ethical governance concerns, and data privacy risks. Overall, AI functions as an augmentative tool that strengthens professional nursing judgment rather than replacing it. Sustainable integration in community and home nursing care requires digital competence, regulatory alignment, and human-centered implementation strategies.